Model Reference Adaptive Control with Smith Predictor Using the MIT Rule for a Two-Degree-of-Freedom Shake Table - Nuñez Rodríguez, Rafael Augusto (Ingeniería Solidaria, 2014)
Shake tables have generally been used for civil structure analysis, as they allow the user to estimate and analyze a scale model’s dynamic response to a real earthquake. Many of these systems are built using linear actuators which allow the application of classic control techniques. This article details the implementation of a model reference adaptive control (MRAC) system using the MITC rule with Smith predictor on a two degree-of-freedom shake table powered by a three-phase motor coupled to a cam and connecting rod mechanism. The non-linear characteristics of this equipment, and the high degree of uncertainty and dead time, require the use of advanced control techniques. The MIT rule is the original focus for the MRAC, and a Smith predictor scheme is simultaneously used to compensate for system response delays. The control system is implemented on a 32-bit Microchip® platform connected to a host.
Keywords: adaptive control; cam and connecting rod mechanism; Smith predictor; MIT rule